2013
DOI: 10.1615/critrevimmunol.2013006813
|View full text |Cite
|
Sign up to set email alerts
|

The Immune System in the Pathogenesis of Ovarian Cancer

Abstract: Clinical outcomes in ovarian cancer are heterogeneous even when considering common features such as stage, response to therapy, and grade. This disparity in outcomes warrants further exploration into tumor and host characteristics. One compelling host characteristic is the immune response to ovarian cancer. While several studies have confirmed a prominent role for the immune system in modifying the clinical course of the disease, recent genetic and protein analyses also suggest a role in disease incidence. Rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
52
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 197 publications
(216 reference statements)
1
52
0
1
Order By: Relevance
“…As we and others have shown, ovarian cancer creates a pronounced immune suppressive TME (17) and of many factors, the cytokine IL-10 has been correlated with volume of ascites, poor survival and relapse (18–20). In the ID8 murine model of ovarian cancer, we have seen that IL-10 is present at high levels in both the blood serum and ascites.…”
Section: Introductionmentioning
confidence: 88%
“…As we and others have shown, ovarian cancer creates a pronounced immune suppressive TME (17) and of many factors, the cytokine IL-10 has been correlated with volume of ascites, poor survival and relapse (18–20). In the ID8 murine model of ovarian cancer, we have seen that IL-10 is present at high levels in both the blood serum and ascites.…”
Section: Introductionmentioning
confidence: 88%
“…Specifically, patients treated with surgical resection and chemotherapy, whose tumors contained CD3 + T cells, had a significantly higher 5-year survival rate compared to patients whose tumors lacked infiltrating T cells [8,9]. Furthermore, when the subtype CD8 + TILs were analysed, they showed a stronger association with prolonged survival than the whole CD3 + TIL population [10].…”
Section: Introductionmentioning
confidence: 99%
“…Patients with advanced OC exhibit a progressively deficient immune response which is believed to be associated with its poor outcome. Recent studies have suggested that tumors capable of creating an immunosuppressive microenvironment can escape immune surveillance and undergo progression [2, 3]. Therefore, a better understanding of how an immunosuppressive microenvironment develops and functions in cancer is required.…”
Section: Introductionmentioning
confidence: 99%